Atrioventricular Node Dysfunction in Adult Patient with Atrial Septal Defect: Focus on Pacemaker Management - Jomanzyah MUA., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Atrioventricular Node Dysfunction in Adult Patient With Atrial Septal Defect: Focus on Pacemaker Management